Brazil : Can Providing Teachers with Feedback and Coaching Improve Learning? - World Bank (World Bank, Washington, DC, 2018)
Improving the classroom effectiveness of teachers is a key part of improving student learning. How to get this right is a core challenge for education systems. Teacher quality varies widely and teachers may not know the best teaching practices and how to keep students on task and engaged with the material. Especially in low-income countries or regions, teachers may not have the resources, knowledge or motivation to teach effectively.Governments and development partners invest heavily in teacher training. Evidence on which approaches raise student learning is crucial for education progress.In Brazil, policymakers from the Ceará state government worked with the World Bank and the Brazilian nongovernmental Lemann Foundation to design a programto improve secondary school teacher effectiveness. The program provided feedback to teachers on their classroom practices and gave them access to expert educational coaching through one-on-one sessions delivered via Skype. With support from the World Bank’s Strategic Impact Evaluation Fund, the World Bank team incorporated an impact evaluation into the program to test the effectiveness of the approach. The evaluation found that over the course of the year, teachers’ classroom practices improved, teachingtime increased, students were more engaged, and students’standardized test scores improved. Based on the results,the Ceará government made the program’s curriculum and technology available to municipal schools in 2017.